Plant and marine-derived natural products: sustainable pathways for future drug discovery and therapeutic development - Ahmad, Muhammad; Tahir, Maleha; Hong, Zibin; Zia, Muhammad Anjum; Rafeeq, Hamza; Ahmad, Muhammad Shaheez; Rehman, Saif ur; Sun, Junming (Frontiers in Pharmacology, 2025)
Plant- and marine-derived natural products are rich sources of bioactive compounds essential for drug discovery. These compounds contain complex mixtures of metabolites, which collectively contribute to their pharmacological properties. However, challenges arise in the isolation of individual bioactive compounds, owing to their intricate chemistry and low abundance in natural extracts. Despite these limitations, numerous plant and marine-derived compounds have achieved regulatory approval, particularly for treating cancer and infectious diseases. This review explores the therapeutic potential of plant and marine sources along with innovative extraction and isolation methods that support sustainable drug development. Future perspectives will highlight the role of responsible innovation, artificial intelligence, and machine learning in advancing drug discovery, underscoring the importance of continued research to meet global health needs.